1998
DOI: 10.2134/jeq1998.00472425002700050015x
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of Carbon Dioxide, Nitrous Oxide, and Methane in Grass Sod and Winter Wheat‐Fallow Tillage Management

Abstract: Cropping and tillage management can increase atmospheric CO2, N2O, and CH4 concentrations, and contribute to global warming and destruction of the ozone layer. Fluxes of these gases in vented surface chambers, and water‐filled pore space (WFPS) and temperature of survace soil were measured weekly from a long‐term winter wheat (Triticum aestivum L.)‐fallow rotation system under chemical (no‐tillage) and mechanical tillage (noninversion subtillage at 7 to 10 cm or moldboard plowing to 15 cm) follow management an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
126
5
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(165 citation statements)
references
References 0 publications
30
126
5
4
Order By: Relevance
“…Our study showed that tillage treatments affect soil CO2 emissions, which agrees with several other studies [15,39], where CO2 release varied with agricultural practices. Figure 3 presents two-year average soil C-CO2 emissions (n = 48) considering tillage treatments.…”
Section: Influence Of Tillage Treatment On Soil C-co2 Emissionssupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed that tillage treatments affect soil CO2 emissions, which agrees with several other studies [15,39], where CO2 release varied with agricultural practices. Figure 3 presents two-year average soil C-CO2 emissions (n = 48) considering tillage treatments.…”
Section: Influence Of Tillage Treatment On Soil C-co2 Emissionssupporting
confidence: 93%
“…Emissions amounted to 17.1 kg ha´1 day´1 during corn cultivation, which is in accordance with the value (19.4 kg ha´1 day´1) obtained by Ussiri and Lal [22] during corn cultivation in Ohio. During winter wheat growing season, soil C-CO 2 emissions amounted to 28.7 kg ha´1 day´1 which is higher than results obtained by Kessavalou et al [15], who determined that mean annual CO 2 emissions from wheat-fallow at Sidney, NE, ranged from 6.9 to 20.1 kg C ha´1 day´1.…”
Section: Influence Of Vegetation On Soil C-co 2 Emissionscontrasting
confidence: 57%
See 1 more Smart Citation
“…Microclimatic conditions had mostly weak or modest impact on soil CO 2 emission. Similar results were reported by Kessavalou, A. et al (1998) Bilandžija, D. et al (2014) and Bilandžija, D. (2015). Of all tested functions, best type of correlation between soil CO 2 emissions and microclimatic factors, showed to be the second order polynomial correlation, except for soil water content.…”
Section: Discussionsupporting
confidence: 89%
“…CH 4 flux measured between 9:00 AM and 13:00 PM can approximately represent the average flux of the day [13,37,38]. Based on the observation data and the integral quadrature between dynamic curves of the CH 4 uptake flux and the time axis [39], we can get average daily uptake flux.…”
Section: Ch 4 Fluxes Of Different Treatments and The Influence Of Prementioning
confidence: 99%